(untitled) (REMUNOM, 2023)
This research looks to describe how school and family are dealing with sexual education for teenagers, considering the difficulties of approaching this thematic in an open and assertive manner. Beyond the literature review, it was realized a qualitative field research, classified as descriptive as for the purposes. The results show different perspectives about this topic of discussion. The majority of the adolescents would rather talk about sexuality with friends or search the internet for occasional doubts, the parents have a hard time trying to talk about this topic with their children, and the teachers report difficulty and fear of talking about sexuality in the classroom, recognizing the necessity of capacitations. It can be stated that the teenagers are ready for the extension and naturalization of sexual education, although the parents and the school are adverse in some aspects. Both family and school have shown the necessity of communication among them, but the school workers consider the family as a hindrance when this topic is mentioned.